2015
DOI: 10.18632/oncotarget.5150
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of glutamine metabolism counteracts pancreatic cancer stem cell features and sensitizes cells to radiotherapy

Abstract: Pancreatic ductal adenocarcinoma (PDAC) cells utilize a novel non-canonical pathway of glutamine metabolism that is essential for tumor growth and redox balance. Inhibition of this metabolic pathway in PDAC can potentially synergize with therapies that increase intracellular reactive oxygen species (ROS) such as radiation. Here, we evaluated the dependence of pancreatic cancer stem cells (PCSCs) on this non-canonical glutamine metabolism pathway and researched whether inhibiting this pathway can enhance radios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 42 publications
1
72
0
Order By: Relevance
“…Gordon et al showed that the largest CSC subpopulation in breast cancer exhibited a glycolytic gene expression profile even in the presence of ample oxygen, suggesting preferential reliance on glycolysis. Li et al showed additionally dependence of pancreatic cancer stem cells (PCSCs) on glutamine; the authors showed that glutamine deprivation negatively affected self‐renewal and expression of stemness‐related genes, increased apoptosis, and enhanced PCSC radiosensitivity.…”
Section: Immunometabolismmentioning
confidence: 99%
“…Gordon et al showed that the largest CSC subpopulation in breast cancer exhibited a glycolytic gene expression profile even in the presence of ample oxygen, suggesting preferential reliance on glycolysis. Li et al showed additionally dependence of pancreatic cancer stem cells (PCSCs) on glutamine; the authors showed that glutamine deprivation negatively affected self‐renewal and expression of stemness‐related genes, increased apoptosis, and enhanced PCSC radiosensitivity.…”
Section: Immunometabolismmentioning
confidence: 99%
“…One of the experimental approaches for obtaining CSC-like properties in cells is to culture cancer cells in suspension, resulting in spheroid-shaped cells [68]. Indeed, a previous study has suggested that metabolic profiles in spheroid-derived cells from ovarian serous adenocarcinoma were different from those in cancer cells that were cultured in adherent plates [8].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the differences in the metabolites generated under 3D and 2D conditions were attributable to the amino acids that are essential for actively and efficiently carrying out TCA cycle reactions; namely, serine, aspartate, glutamate and glutamine [6, 915]. Indeed, these amino acids were significantly increased in 3D conditions when compared to 2D conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While GLS inhibitors may serve as monotherapies, their combination with other concurrent therapies such as radiotherapy, chemotherapy or immunotherapy is equally intriguing. With respect to radio‐ and chemotherapy, studies in PDAC have demonstrated that GLS inhibition leads to increased radio‐sensitivity, largely due to increased ROS generation, an aspect likely linked to alterations in glutathione biosynthesis, a well‐documented contributor to drug resistance . Indeed, studies in triple‐negative breast cancer have demonstrated considerable effects of CB‐839 on reducing glutathione levels in a cell line‐dependent manner .…”
Section: Small Molecule Inhibitors: Targeting Both Cancer and Immune mentioning
confidence: 99%